2000
DOI: 10.1039/b000035n
|View full text |Cite
|
Sign up to set email alerts
|

The deuterium quadrupole coupling constant in liquid ammonia

Abstract: The presence of hydrogen bonds in liquid ammonia is not without controversy. Probes for hydrogen bonds are the gas to liquid shift and the temperature dependence in the liquid of the deuterium quadrupole coupling constant (DQCC). Using a new NMR method, the Ðrst reliable results for the DQCC in liquid heavy ammonia were obtained for six temperatures between 237 and 293 K. The value of 232(1) kHz at 237 K amounts to only 80% of the gas phase value. A small temperature dependence of about 0.1 kHz K~1 in the liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…Using a combination of ab initio calculations and molecular dynamics simulations Huber 32,33 obtained a value of 252 kHz in excellent agreement with experimental data. For ammonia we obtained a gas to liquid shift of about 14.0 kHz which is smaller than shifts calculated from measured gas (282 kHz, 36 290.6 kHz 37 ) and liquid (232 kHz, 38 245 kHz 39 ) phase data. Experimental liquid association shifts of the dqcc for the weak hydrogen bonded hydrogen sulfide and the non-H-bonded phosphine are not known.…”
Section: B Thermodynamic Propertiescontrasting
confidence: 62%
“…Using a combination of ab initio calculations and molecular dynamics simulations Huber 32,33 obtained a value of 252 kHz in excellent agreement with experimental data. For ammonia we obtained a gas to liquid shift of about 14.0 kHz which is smaller than shifts calculated from measured gas (282 kHz, 36 290.6 kHz 37 ) and liquid (232 kHz, 38 245 kHz 39 ) phase data. Experimental liquid association shifts of the dqcc for the weak hydrogen bonded hydrogen sulfide and the non-H-bonded phosphine are not known.…”
Section: B Thermodynamic Propertiescontrasting
confidence: 62%
“…Although in liquids one would expect a decrease of the quadrupole coupling constant with the increase of the temperature due to the averaging at higher temperatures, an increase of the coupling constant in the range of 0.01-0.08 kHz K À1 was observed in this work as a result of the variation of A quad with temperature. Although unexpected, in the literature similar coupling constant increase effects have already been described for other systems: Ludwig et al had found a linear increase of the deuteron quadrupole coupling constant of water in a water and dimethyl sulfoxide mixture of 0.08 kHz K À1 in the temperature range from 188 K to 308 K. 33 In liquid ammonia a linear temperature dependence of 0.1 kHz K À1 was determined by Hardy et al for the deuteron quadrupole coupling constant in the temperature range from 237 K up to 293 K. 34 A linear temperature dependence of the 7 Li quadrupolar coupling constant of 0.05 kHz K À1 above 330 K was found by Arun et al in an intercalated polymer electrolyte (IPE), Cd 0.75 PS 3 Li 0.5 (PEO). 35 Further examples of the increase of the quadrupole coupling constant in liquids can be found elsewhere.…”
Section: Model Including a Temperature Dependent Prefactormentioning
confidence: 78%